2015
DOI: 10.1523/jneurosci.2431-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Neuromuscular Dysfunction in Krabbe Disease

Abstract: The atrophy of skeletal muscles in patients with Krabbe disease is a major debilitating manifestation that worsens their quality of life and limits the clinical efficacy of current therapies. The pathogenic mechanism triggering muscle wasting is unknown. This study examined structural, functional, and metabolic changes conducive to muscle degeneration in Krabbe disease using the murine (twitcher mouse) and canine [globoid cell leukodystrophy (GLD) dog] models. Muscle degeneration, denervation, neuromuscular [n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 74 publications
1
40
0
1
Order By: Relevance
“…In fact, impaired protein kinase C activity (Yamada et al, ; White et al, ) and increased basal location of TrkA in lipid rafts were found in twitcher cells with defective activation of the downstream ERK1/2 and AKT pathways (Teixeira et al, ). It is notable that the defect in ERK and AKT activation was not restricted to KD neurons; it has also been described in mouse oligodendrocyte progenitor cells exposed to psychosine (Zaka et al, ), and, more recently, the twitcher muscle was also shown to have inactivation of the AKT pathway (Cantuti‐Castelvetri et al, ). In twitcher dorsal root ganglion neurons expressing Rab5‐GFP, a marker of early endosomes retained in Trk‐containing endosomes, not only was a decreased density of Rab5‐containing (Rab5 + ) vesicles observed but also a decreased percentage of Rab5 + vesicles containing TrkA was found, further suggesting that the endocytic pathway, specifically the formation of Trk‐signaling endosomes, was impaired (Teixeira et al, ).…”
Section: Psychosine Accumulation In Kd Neurons: Altered Lipid Raft Stmentioning
confidence: 96%
See 2 more Smart Citations
“…In fact, impaired protein kinase C activity (Yamada et al, ; White et al, ) and increased basal location of TrkA in lipid rafts were found in twitcher cells with defective activation of the downstream ERK1/2 and AKT pathways (Teixeira et al, ). It is notable that the defect in ERK and AKT activation was not restricted to KD neurons; it has also been described in mouse oligodendrocyte progenitor cells exposed to psychosine (Zaka et al, ), and, more recently, the twitcher muscle was also shown to have inactivation of the AKT pathway (Cantuti‐Castelvetri et al, ). In twitcher dorsal root ganglion neurons expressing Rab5‐GFP, a marker of early endosomes retained in Trk‐containing endosomes, not only was a decreased density of Rab5‐containing (Rab5 + ) vesicles observed but also a decreased percentage of Rab5 + vesicles containing TrkA was found, further suggesting that the endocytic pathway, specifically the formation of Trk‐signaling endosomes, was impaired (Teixeira et al, ).…”
Section: Psychosine Accumulation In Kd Neurons: Altered Lipid Raft Stmentioning
confidence: 96%
“…As previously discussed, independent studies have shown that the AKT‐GSK3β pathway is dysregulated in KD, with neurons (Teixeira et al, ), oligodendrocyte precursors (Zaka et al, ), and muscle (Cantuti‐Castelvetri et al, ) presenting decreased AKT activation and/or the resulting increased GSK3β activity. These findings raise the possibility that inhibiting GSK3β could be considered a relevant therapeutic strategy in KD.…”
Section: Advancing Toward the Correction Of Neuronal Pathology In Kdmentioning
confidence: 99%
See 1 more Smart Citation
“…Defective autophagosome–lysosome fusion resulting in accumulation of toxic metabolites and cell death has been proposed for several neurodegenerative LSD (Settembre et al, ) but has never been reported for GLD. These pathways may indeed be implicated in the decline of cellular function that ultimately results in the appearance of clinical symptoms and are worth investigating in appropriate GLD models. g)Psychosine contributes to muscle pathology acting at multiple levels (decreasing Akt signaling and increasing ubiquitination of muscle proteins and their degradation), ultimately resulting in presynaptic and postsynaptic defects in the neuromuscular junction (Cantuti‐Castelvetri et al, ).…”
Section: Gld Pathophysiologymentioning
confidence: 99%
“…Also, they might be beneficial to slow the progression of the disease, until enzymatic activity is effectively restored and the storage defects have been corrected. In this perspective, pharmacological modulation of the ERK1/2, AKT, and/or GSK3β pathways, which are affected (inhibited or hyperactivated) as a consequence of psychosine accumulation and contribute to neuronal (Cantuti Castelvetri et al, ; Teixeira et al, ), oligodendroglial (Zaka et al, ), and muscular (Cantuti‐Castelvetri et al, ) dysfunction in Twitcher mice may constitute a promising target to complement therapies for Krabbe's disease.…”
Section: Future Perspectives: Enhancing Gene Therapy Strategies and Omentioning
confidence: 99%